The Circular RNA Circ_0043947 Promoted Gastric Cancer Progression by Sponging miR-384 to Regulate CREB1 Expression - Chongxin Zhang; Fan Zhang; Yukun Li; Pengfei Yang; Yang Liu; Wenxiao Yang (Gut and Liver)
Background/Aims: The occurrence and development of circular RNAs in gastric cancer (GC) has attracted increasing attention. This study focused on investigating the biological role and molecular mechanism of circ_0043947 in GC. Methods: The expression levels of circ_0043947, miR-384 and CAMP response element binding protein (CREB1) were determined by quantitative real-time polymerase chain reaction or Western blotting. Cell proliferation, migration, and invasion, the cell cycle and apoptosis were determined using a cell counting kit-8 assay, 5-ethynyl-2'-deoxyuridine assay, colony formation assay, wound healing assay, transwell assay, and flow cytometry assay. The interaction between miR-384 and circ_0043947 or CREB1 was verified by dual-luciferase reporter assay and RNA pull-down assay. The in vivo assay was conducted using a xenograft mouse model. Results: Circ_0043947 and CREB1 expression levels were significantly upregulated, whereas miR-384 expression levels were downregulated in GC tissues and cells. Functionally, knockdown of circ_0043947 inhibited cell proliferation, migration and invasion and induced G0/G1 phase arrest and apoptosis in vitro. Circ_0043947 could upregulate CREB1 expression by directly sponging miR-384. Rescue experiments showed that a miR-384 inhibitor significantly reversed the inhibitory effect of si-circ_0043947 on GC progression, and CREB1 overexpression significantly reversed the inhibitory effect of miR-384 mimics on the progression of GC cells. Furthermore, silencing of circ_0043947 inhibited tumor growth in vivo. Conclusions: Circ_0043947 acted as an oncogenic factor in GC to mediate GC cell proliferation, migration, and invasion, the cell cycle and apoptosis by regulating the miR-384/CREB1 axis. Circ_0043947 may be a potential target for GC diagnosis and therapy.